A review of stability-enhanced luminescent materials: fabrication and optoelectronic applications. Issue 17 (15th April 2019) - Liu, Jiahui; Yang, Zunxian; Ye, Bingqing; Zhao, Zhiwei; Ruan, Yushuai; Guo, Tailiang; Yu, Xuebin; Chen, Gengxu; Xu, Sheng
Abstract : This review mainly focuses on the recent important work on stability-enhanced strategies of luminescent materials. Various strategies on the fabrications have been summarized and corresponding optoelectronic applications are presented. Abstract : Luminescent materials such as Cd-based quantum dots, CuInS2 quantum dots, and perovskite-based materials play an important role as an exceptional class of optoelectronic materials due to their unique and novel characteristics for optoelectronic applications. However, a key challenge for luminescent materials and devices is their poor long-term stability, which is typically attributed to the irreversible changes of surface ligands or chemical structure against oxygen and moisture when exposed to ambient atmosphere. Thus, this review mainly focuses on recent important work on the stability-enhanced strategies of luminescent materials. Various strategies for their fabrication, including surface engineering and surface coating routes have been summarized, followed by their advantages and challenges. Furthermore, the corresponding optoelectronic applications of these promising stability-enhanced luminescent materials in light-emitting diodes, photodetectors, solid-state lighting chips, and solar cells were also reviewed. Afterward, the outlook and perspective are presented.